From Classroom to Career: A Tracer Study on The Acchievements and Employment Patterns of BS in Accountancy, BS in Accounting Information System and BS in Entrepreneurship Graduates - Bongalonta, Michael B.; Bongalonta, Michelle M.; Gigantoca, Santos; Naz, Graham M.; Melitante, Allyboy; Inocentes, Marilyn N.; Sales, Diana V.; Despuig, Led L.; Fulgar, Abegail A.; Delmonte, Gloriane; Ambrose, Benjamin; Barcarse, Eula Ceelin; Balaguer, Renebec A.; Especial, Mary Ann D.; Guim, Shalom C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study evaluates the achievements and employment patterns of BS Accountancy, BS in Accounting Information Systems, and BS in Entre-preneurship graduates from Sorsogon State University Bulan Campus (2019-2023). It assesses the extent of Program Educational Objec-tives (PEOs) achievement, analyzes employment rates, and gathers employer feedback on graduates' competencies. Using a descriptive-survey design, data were collected from recent graduates, employers, and notable alumni. Findings indicate high success in achieving PE-Os, strong employment rates, and positive employer evaluations. Recommendations include curriculum updates, enhanced industry partnerships, and expanded career services to further support grad-uate success.